Analisis SWOT Terhadap Pelaksanaan Strategi Pemasaran Madu Kelulut Pada Kelompok Usaha Desa Petak Puti - Fendy Hariatama; Merisa Oktaria; Windy Utami Putri; Rinto Alexandro; Rendy Prayogo; Hendrowanto Nibel (FKIP, Universitas Palangka Raya, 2022)
The purpose of this study was to obtain data about the marketing strategy applied by the honey kelulut business group community, to know the implementation of the marketing strategy, to know the results of the SWOT analysis on the implementation of the marketing strategy and to find out the problems faced by the kelulut honey business group community in Petak Puti Village. This study uses a descriptive research method with a qualitative approach or data collection, interviews, observations and documentation. The subject of this research is the community of the honey kelulut business group in Petak Puti Village. The data analysis technique in this study used an interactive qualitative descriptive data analysis model consisting of three concurrent activity lines, namely: data reduction, data presentation, and conclusion drawing. Based on the results of research and interviews, it was shown that at first this kelulut honey bee colony was an aid from the government. How to add a colony apart from government assistance, is also looking for colonies of honey bee kelulut in the forest or breaking up colonies of honey bee kelulut that already exists. In addition to maintaining stup assistance from the government, they also look for kelulut honey bee colonies in the forest around the village and break up existing colonies, so that these colonies can later grow. As well as planting flowers that have enough pollen so that it can increase the productivity of the honey produced. The influencing factors are the cleanliness of the stup, the safety of the stup from rainy or hot weather, and also guarding against nuisance animal attacks. There are two kinds of stup, namely stup made of wood logs taken from the forest which directly have the colony and some are made of boards, the stup is for the transfer of the colony. The post-harvest honey process is filtered into closed jars, allowed to stand for 2-3 days to reduce foam at the time of harvest, then poured into packaged bottles. The group entrusts the marketing of honey to the assistants, so that the assistants who market to the City of Palangka Raya and its surroundings go through agents/collectors in that city